Improvement of Nutrition Perception in Adult Women with Health Belief Model Approach - Nuriannisa, Farah; Yuliani, Kartika; Raharjeng, Sa'bania Hari; Chasanatussy, Mustika; Awaliah Ridlwan, Beta Wardah; Adkhatus, Nanda; Anjali, Shafira Nurhaliza (LP2M INSURI Ponorogo, 2023)
Adult has higher risk of degenerative diseases. Healthy diet is a way to prevent degenerative diseases. Based on the interviews with the head of RT 01 RW 02 Dukuh Menanggal Surabaya, there was no nutrition education conducted, thus knowledge and implementation of healthy eating in that area was low. Improvement in healthy diet can be done through nutrition education using Health Belief Model approach. The purpose of this activity was to increase participants' perceptions of nutrition and health. The participants were 17 adult women from RT 01 RW 02 Dukuh Menanggal Surabaya. Nutrition education regarding Pedoman Gizi Seimbang was carried out using Health Belief Model, as well as demonstrations of nutritional status measurement. The activity’s results showed that majority of participants had high nutritional status. Based on the evaluation with the pre-post test, participants' perceptions of vulnerability, severity, and benefit was elevated, while the perception of barrier declined. There was an improvement in participants' perceptions of diet and health as much as 201.3%. In addition, regular monitoring of nutritional status in adults must be carried out as screening of nutrition and health problem risk.